The Effectiveness of Arabic Speaking Skill Instruction: Using Developed Animated Cartoons - K. M. A. AHAMED ZUBAIR (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
Speaking skill (Maharat al-Kalam) is a fundamental component of Arabic language acquisition, yet many non-native learners face difficulties due to monotonous teaching methods and lack of appropriate instructional media. This study aims to determine the effectiveness of using developed animated cartoons as a medium for teaching Arabic speaking skills. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at the Department of Arabic, The New College, Chennai, India, involving 30 male students. Data collection techniques included interviews, observations, and pre-test and post-test oral assessments. The results showed a significant improvement in students' speaking skills after the intervention. The mean pre-test score was 59.72 (categorized as